Earthworm Abundance Changes Depending on Soil Management Practices in Slovenian Vineyards - Stanko Vršič; Marko Breznik; Borut Pulko; Jesús Rodrigo-Comino (Agronomy, 2021)
Earthworms are key indicators of soil quality and health in vineyards, but research that considers different soil management systems, especially in Slovenian viticultural areas is scarce. In this investigation, the impact of different soil management practices such as permanent green cover, the use of herbicides in row and inter-row areas, use of straw mulch, and shallow soil tillage compared to meadow control for earthworm abundance, were assessed. The biomass and abundance of earthworms (m2) and distribution in various soil layers were quantified for three years. Monitoring and a survey covering 22 May 2014 to 5 October 2016 in seven different sampling dates, along with a soil profile at the depth from 0 to 60 cm, were carried out. Our results showed that the lowest mean abundance and biomass of earthworms in all sampling periods were registered along the herbicide strip (within the rows). The highest abundance was found in the straw mulch and permanent green cover treatments (higher than in the control). On the plots where the herbicide was applied to the complete inter-row area, the abundance of the earthworm community decreased from the beginning to the end of the monitoring period. In contrast, shallow tillage showed a similar trend of declining earthworm abundance, which could indicate a deterioration of soil biodiversity conditions. We concluded that different soil management practices greatly affect the soil’s environmental conditions (temperature and humidity), especially in the upper soil layer (up to 15 cm deep), which affects the abundance of the earthworm community. Our results demonstrated that these practices need to be adapted to the climate and weather conditions, and also to human impacts.